2017
DOI: 10.2174/1570161115666170201122750
|View full text |Cite
|
Sign up to set email alerts
|

Functional Upregulation of STIM-1/Orai-1-Mediated Store-Operated Ca2+ Contributing to the Hypertension Development Elicited by Chronic EtOH Consumption

Abstract: These findings suggest that hypertrophic aortic remodeling and abnormal contraction triggered mainly by Ca2+ overload via STIM-1/Orai-1-mediated SOCE through SOCCs are involved hypertension developed by EtOH consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…were calculated by integrating the transients versus time during the stimulus duration for each experiment. The SOCE slope (increase or decrease) parameter was fitted by the GraphPad Prism software using the one-phase association equation [2]. Data represents the mean ± SEM of the minimum of three independent experiments.…”
Section: Data Analyses and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…were calculated by integrating the transients versus time during the stimulus duration for each experiment. The SOCE slope (increase or decrease) parameter was fitted by the GraphPad Prism software using the one-phase association equation [2]. Data represents the mean ± SEM of the minimum of three independent experiments.…”
Section: Data Analyses and Statisticsmentioning
confidence: 99%
“…It is well established that calcium (Ca 2+ ) handling is one of the most widespread transducing systems, regulating a wide range of cell biology and pathophysiologic processes [1][2][3][4][5]. Enamel is the most calcified vertebrate tissue, requiring a steady supply of Ca 2+ for its mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Increased SOCE was detected in transient receptor potential 3 and 5 channels in monocytes of patients with essential hypertension [25]. Overexpression of STIM-1 resulted in hypertrophic arterial remodeling and cardiac hypertrophy in chronic ethanol-induced hypertensive rats [26]. For example, gastrodin, an agent used to treat hypertension, was found to suppress SOCE by reducing the expression of STIM-1 in a phenyl-ephrine-induced mouse model of cardiac hypertrophy [27].…”
Section: Discussionmentioning
confidence: 99%
“…We found that A-769662 inhibited the steady-state contraction induced by CPA in FA in a manner similar to the selective store-operated Ca 2+ channel inhibitor, YM-58483 ( Harper and Poole, 2011 ). Notably, YM-58483 was shown to inhibit STIM-1/Orai-1 induced store-operated Ca 2+ entry in ethanol-treated rats ( Souza Bomfim et al, 2017 ). Thus, we propose that one mechanism by which A-769662 causes VSM relaxation is via inhibition of store-operated Ca 2+ entry.…”
Section: Discussionmentioning
confidence: 99%